Proximal Trauma Increases Risk of Venous Thrombosis in Soft Tissue Reconstruction of Open Lower Limb Fractures - Yalcin, Nilay G.; Bruscino-Raiola, Frank; Ferris, Scott (Frontiers in Surgery, 2021)
Lower limb salvage after major trauma is a complex undertaking. For patients who have suffered multi-level trauma to their lower limb we postulated that pelvic injury or ipsilateral lower limb injury proximal to the site of a free flap may increase the rate of post-operative complications. All patients who underwent lower limb free flap reconstruction as a result of acute trauma between January 2010 and December 2017 were included. The patients were divided into the study group (50 patients), who sustained a lower limb or pelvic injury proximal to the free flap site, and control group (91 patients) who did not sustain proximal lower limb or pelvic trauma. Complication rates were compared between the two groups. Overall, the proximal trauma group anastomotic thrombosis rate of 18.0% was significantly higher than the control group thrombosis rate of 2.2%. There was no statically significant difference in rates of hematoma, swelling or infection. Flap loss rate in the proximal trauma group was 4.0%, compared to the control group at 2.2%. All patients with a failed flap went onto have a successful reconstruction with a subsequent flap in the acute admission and there were no amputations. In the proximal injury study group despite the significantly increased rate of microvascular thrombosis requiring revision, the ultimate primary free flap survival rate was still 96%. Overall, severe coexisting proximal trauma predicted a higher venous microvascular complication rate but was not a contraindication to limb salvage.